General Theorems on the Existence and Uniqueness of Solutions of Impulsive Differential Equations - Slyusarchuk, V. E. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We study the Cauchy problem for impulsive differential equations in the general case.